2017
DOI: 10.2991/ijndc.2017.5.2.3
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Cross-Layer QoS-Aware Protocol with Traffic-Differentiation-Based for Energy Efficient Communication in WSNs

Abstract: Despite an increase in energy efficiency of WSNs research in couple of last years, still the key challenge in the design of WSNs remains to maximize the quality of service (QoS) and energy efficiency of network system. The layered strength and functionality collaboration is commonly considered as one of the most promising techniques for dealing with the given challenge to increase the duration between recharging battery and improve energy efficiency in order to prolong the sensor nodes and network lifetime. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In literature we found that several protocols have been considered the energy efficiency parameter as a main attribute design of a protocol [1], [2], [4], [7], [16]. For example, we focus on the protocol presented in [1], [7] and [16] by authors, as we used to target in our work.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In literature we found that several protocols have been considered the energy efficiency parameter as a main attribute design of a protocol [1], [2], [4], [7], [16]. For example, we focus on the protocol presented in [1], [7] and [16] by authors, as we used to target in our work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4. According to [3][4], synchronization of frame is maintained by virtual clustering. During virtual clustering, sensor nodes can handle different schedule from its neighbour hop and each node is given a unique identification number (ID).…”
Section: Protocol Stack Of J-rmpmentioning
confidence: 99%
See 3 more Smart Citations